2023
DOI: 10.1002/jnr.25170
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal injection of IL‐1β upregulates Siah1‐mediated degradation of synaptophysin by activation of the ERK signaling in male rat

Abstract: Interleukin-1β (IL-1β) has been described to exert important effect on synapses in the brain. Here, we explored if the synapses in the hippocampus would be adversely affected following intracerebral IL-1β injection and, if so, to clarify the underlying molecular mechanisms. Adult male Sprague-Dawley rats were divided into control, IL-1β, IL-1β + PD98059, and IL-1β + MG132 groups and then sacrificed for detection of synaptophysin (syn) protein level, synaptosome glutamate release, and synapse ultrastructure by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…SYN is well known for its involvement in synaptic plasticity mechanisms, and it is one of the most crucial proteins within synaptic vesicles. The synaptic vesicle is a site within the presynaptic neuron where neurotransmitters are stored 11 . An increase in SYN levels can enhance neurotransmitter secretion into the synaptic space, thereby facilitating synaptic transmission between neurons 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SYN is well known for its involvement in synaptic plasticity mechanisms, and it is one of the most crucial proteins within synaptic vesicles. The synaptic vesicle is a site within the presynaptic neuron where neurotransmitters are stored 11 . An increase in SYN levels can enhance neurotransmitter secretion into the synaptic space, thereby facilitating synaptic transmission between neurons 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, microtubule-associated protein 2 (MAP2) is a protein enriched in dendrites and serves as a marker for synaptic plasticity 10 . On the other hand, synaptic proteins, including synaptophysin (SYN), are involved in synaptic plasticity and transmission 11 . Any changes in the levels of these proteins may be associated with abnormal dendritic and synaptic function.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, a significant decrease in estrogen levels disrupts immune homeostasis, particularly the levels of the immune factors TNF-α, IL-1β, IL-4, IL-6, IL-10 and IL-18 through the ERα/ERβ/GPER-associated NLRP3/NF-κB signaling pathway, which involves many signaling molecules, such as TLR2, TLR4, P2X7R, SIRT1, CREB, MS-KIF18A, PI3K, AKT, Gs, cAMP, PKA, PJA1, Serpina3n, Src, and MMP-9 [ 19 24 , 41 , 43 , 44 , 47 49 , 52 , 54 – 56 , 58 ]. Subsequently, the increase of inflammatory cytokine levels causes BBB destruction [ 25 , 62 74 , 165 ], the dysfunction of neurotransmitters such as 5-HT [ 80 85 ], DA [ 86 97 ], NE [ 98 105 ], GABA [ 29 , 30 , 106 113 ] and Glu [ 79 , 114 121 ], BDNF deficiency and dysfunction [ 26 , 128 135 ], and attenuation of neuroplasticity [ 136 146 ], which are key factors in the onset and progression of depression (Fig. 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…9 ). In contrast, Zhou et al reported that IL-1β can upregulate the degradation of the synaptophysin protein by the E3 ligase siah1 via the ERK signaling pathway and subsequently inhibit the release of Glu, which impaired the learning and memory ability of rats [ 121 ].…”
Section: Neurological Impairments Caused By Immune Imbalancementioning
confidence: 99%